Novel analysis of global DNA methylation in the limbic system of the bovine brain - Cantrell, B. A.; McKay, S. D.; Weaber, Robert L.; Funston, R. N.; Lachance, H. (My University, 2017)
There has been limited research focusing on the genetic-environmental interactions in bovine brains. Global DNA methylation has been measured in brains of several species, but has yet to be examined in bovine. The objective of this study was to characterize global DNA methylation in 9 regions of the limbic system in the bovine brain: amygdala, bed nucleus of the stria terminalis, cingulate gyrus, dorsal raphe, hippocampus, hypothalamus, nucleus accumbens, periaqueductal gray, and prefrontal cortex. DNA was extracted from brain and blood samples of 6 Red Angus × Simmental steers (less than 20 mo of age), using the DNA Extraction Kit from Agilent Technologies (Santa Clara, CA) and a phenol chloroform extraction. Percent of global DNA methylation was determined using the MethylFlash Methylated DNA Quantification Kit (Colormetric) from Epigentek (Farmingdale, NY). Varying amounts of global DNA methylation were observed among the 9 functionally distinct regions of the bovine limbic system. Amygdala, bed nucleus of the stria terminalis, cingulate gyrus, dorsal raphe, periaqueductal gray, prefrontal cortex, and nucleus accumbens are all significantly different (P < 0.05) from 1 or more brain tissue type, using a paired t test in SPSS (IBM, Armonk, NY). Conversely, global DNA methylation of blood was not significantly different (P < 0.05) from any brain tissue type. This study shows significant differences in global DNA methylation among different tissue types in the limbic system of the bovine brain. Understanding the differences in global DNA methylation within different tissues in the brain will facilitate future research involving the effects of differential methylation with regard to economically important traits.
Citation: Cantrell, B. A., McKay, S. D., Weaber, R. L., Funston, R. N., & Lachance, H. (2016). Novel analysis of global DNA methylation in the limbic system of the bovine brain. Journal of Animal Science, 94, 43-43. doi:10.2134/jas2016.94supplement443x
Keywords: Bovine; Brain; Methylation; Agriculture